Wound natural healing in treatment of tumor-like hypertrophic scar - Tong Han; De-Feng Lin; Hua Jiang (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Surgical sutures, wound tension, additional skin incisions and other factors may result in recurrence of tumor-like scar. Objective: To investigate the role of wound natural healing therapy in tumor-like hypertrophic scar. Methods: In this study, tumor-like hypertrophic scars of 47 cases were excised completely and the residual wounds were treated with natural healing. The short-term and long-term effects of treatment were evaluated. Results: All cases were successfully cured by natural healing therapy. The healing time of the maximum wound (80mm × 20mm) and the minimal wound (5mm× 5mm) was 25 days and 7 days respectively. The size of new skin scars ranged from 3mm to 11 mm. Clinical followed-up was performed in 34 cases for 36 months. Among them, no recurrence happened in 31 cases and new scar size ranged from 2mm to 8mm, while local recurrence happened in 3 cases whose scar size were less than 5 mm. Study Limitations: The cure rate of the therapy was 91.2%. Conclusion: The wound natural healing therapy is effective in treating tumor-like hypertrophic scar, which can prevent recurrence and has good cosmetic results.